1998
DOI: 10.1042/bj3310513
|View full text |Cite
|
Sign up to set email alerts
|

Purification and partial characterization of a peroxidase from plant cell cultures of Cassia didymobotrya and biotransformation studies

Abstract: An acidic peroxidase (EC 1.11.1.7) produced by cell suspension cultures of Cassia didymobotrya (wild senna) was purified from culture medium collected on the 29th day. The enzyme was shown to be a glycoprotein with a pI of 3.5, a molecular mass of approx. 43 kDa by SDS/PAGE and 50 kDa by gel filtration. The N-terminal sequence was very similar to those of other plant peroxidases. The peroxidase was characterized by a high specificity towards coniferyl alcohol and other natural phenolics such as guaiacol and fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…The presence of seven phenyl protons and twelve phenyl carbons was confirmed with a 1D-NMR spectrum, and a keto group (d = 190.7) was also detected in the 13 C-NMR spectrum. In addition, 1 was also analyzed by HMQC and HMBC experiments, and the obtained data for 1 were very similar to the reported data for the meso form of 3,3¢¢-di(7,4¢-dihydroxyflavanone-3-yl) which had been obtained only as the biotransformation product [8], [9]. Although the signals of H-2, H-2¢¢, H-3 and H-3¢¢ almost could not be observed due to the fixed conformation at 23 8C, these appeared as doublets (d H = 4.86, 2H, d, J = 12.0 Hz, H-2/H-2¢¢ and 3.55, 2H, d, J = 12.0 Hz, H-3/H-3¢¢) on NMR analysis at 80 8C in DMSO-d 6 in a similar manner as reported previously [9], suggesting that H-2, H-2¢¢, H-3 and H-3¢¢ were each located at axial sites.…”
supporting
confidence: 56%
See 2 more Smart Citations
“…The presence of seven phenyl protons and twelve phenyl carbons was confirmed with a 1D-NMR spectrum, and a keto group (d = 190.7) was also detected in the 13 C-NMR spectrum. In addition, 1 was also analyzed by HMQC and HMBC experiments, and the obtained data for 1 were very similar to the reported data for the meso form of 3,3¢¢-di(7,4¢-dihydroxyflavanone-3-yl) which had been obtained only as the biotransformation product [8], [9]. Although the signals of H-2, H-2¢¢, H-3 and H-3¢¢ almost could not be observed due to the fixed conformation at 23 8C, these appeared as doublets (d H = 4.86, 2H, d, J = 12.0 Hz, H-2/H-2¢¢ and 3.55, 2H, d, J = 12.0 Hz, H-3/H-3¢¢) on NMR analysis at 80 8C in DMSO-d 6 in a similar manner as reported previously [9], suggesting that H-2, H-2¢¢, H-3 and H-3¢¢ were each located at axial sites.…”
supporting
confidence: 56%
“…Compound 2 gave similar spectra upon 1 H-NMR, 13 C-NMR and MS analyses as the other biotransformation product, the diastereomer of 1 [9]. Although this biotransformation product of 1 has been reported as the racemate, which showed no optical rotation [9], 2 showed significant dextrorotation (+ 83.28 in MeOH at 25 8C). These findings suggested that 2 might be a diastereomer of 1, but the absolute stereostructure of 2 could not be determined in the present study.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…The reaction was started by the addition of the protein extract at room temperature. Enzymatic activity was calculated with an extinction coefficient of 26.6 mM 21 cm 21 at 470 nm (Vitali et al, 1998). Values are means 6 SE of three replicates.…”
Section: Enzyme Assaysmentioning
confidence: 99%
“…Enzyme activity was assayed according to a published procedure (Vitali et al, 1998) in solutions consisting of 2.8 mL of buffer (0.1 M potassium phosphate buffer, pH 7.0), 50 mL of substrate (18 mM), 50 mL of H 2 O 2 (30%, 1:100 diluted, optical density at 240 nm = 0.4), and 100 mL of crude FaPRX27 extract (1 mg mL 21 ). Reactions were monitored photometrically at the wavelength of maximum absorption of the respective substrates.…”
Section: Enzyme Assaysmentioning
confidence: 99%